The Effectiveness of Cause-Related Marketing in MSME Products in Shaping ESD Awareness Among Urban Consumers of Sensatia Botanica - Luh Anggie Cintya Kamadewi; Ni Putu Meita Krisdayanti; Dita Refieta; Wayan Cherrie Hana Melati; Zahra Syakhira Iswan; Ni Kadek Rizky Ayu Wulandari; Ni Komang Marsari Dewi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study employs a qualitative approach to analyze the effectiveness of Cause-Related Marketing (CRM) on Sensatia Botanica products in shaping Education for Sustainable Development (ESD) awareness among urban consumers. Data were collected through in-depth interviews with five informants, supported by observation and documentation, and analyzed using triangulation techniques. The findings reveal that (1) consumer perceptions of CRM are generally positive and multidimensional, encompassing implicit understanding, perceived added value, and evaluation of authenticity; (2) consumers interpret social value as contributing to society and environmental value as reflecting commitment to sustainable practices, which are internalized into ESD awareness; and (3) CRM effectively fosters ESD awareness through cognitive understanding, emotional engagement, and encouragement toward value-driven consumption, although it remains largely at the level of behavioral intention. Overall, the study highlights CRM’s potential as a non-formal educational tool in promoting sustainability, with its effectiveness influenced by perceived authenticity and consumer trust.